The role of relaxation time corrections for the evaluation of long and short echo time 1H MR spectra of the hippocampus by NUMARIS and LCModel techniques - Jírů, Filip; Dezortová, Monika; Burian, Martin; Hájek, Milan (Magma (New York, N.Y.), 2003)
1H MR spectroscopy is routinely used for lateralization of epileptogenic lesions. The present study deals with the role of relaxation time corrections for the quantitative evaluation of long (TE=135 ms) and short echo time (TE=10 ms) 1H MR spectra of the hippocampus using two methods (operator-guided NUMARIS and LCModel programs). Spectra of left and right hippocampi of 14 volunteers and 14 patients with epilepsy were obtained by PRESS (TR/TE=5000/135 ms) and STEAM (TR/TE=5000/10 ms) sequences with a 1.5-T imager. Evaluation was carried out using Siemens NUMARIS software and the results were compared with data from LCModel processing software. No significant differences between the two methods of processing spectra with TE=135 ms were found. The range of relaxation corrections was determined. Metabolite concentrations in hippocampi calculated from spectra with TE=135 ms and 10 ms after application of correction coefficients did not differ in the range of errors and agreed with published data (135 ms/10 ms: NAA=10.2+/-0.6/10.4+/-1.3 mM, Cho=2.4+/-0.1/2.7+/-0.3 mM, Cr=12.2+/-1.3/11.3+/-1.3 mM). When relaxation time corrections were applied, quantitative results from short and long echo time evaluation with LCModel were in agreement. Signal intensity ratios obtained from long echo time spectra by NUMARIS operator-guided processing also agreed with the LCModel results.
Keywords: Magnetic Resonance Imaging; Diagnosis, Computer-Assisted; Sensitivity and Specificity; magnetická rezonanční tomografie; proteiny nervové tkáně; senzitivita a specificita; Humans; Protons; subtrakční technika; Algorithms; mapování mozku; diagnóza počítačová; Nerve Tissue Proteins; Choline; kreatin; epilepsie temporálního laloku; Subtraction Technique; interpretace obrazu počítačem; Models, Biological; dospělí; protony; Hippocampus; kyselina asparagová; lidé; magnetická rezonanční spektroskopie; cholin; hipokampus; reprodukovatelnost výsledků; Creatine; Brain Mapping; Adult; Image Interpretation, Computer-Assisted; Reproducibility of Results; biologické modely; Epilepsy, Temporal Lobe; algoritmy; Aspartic Acid; Magnetic Resonance Spectroscopy